Characteristics of sleeping sites and sleeping trees selected by Celebes crested macaques (Macaca nigra) in Tangkoko, North Sulawesi, Indonesia - INDIRA NURUL QOMARIAH; DYAH PERWITASARI-FARAJALLAH; ENTANG ISKANDAR; JULIETTE MORGAN BERTHIER (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Qomariyah IN, Perwitasari-Farajallah D, Iskandar E, Berthier JM. 2023. Characteristics of sleeping sites and sleeping trees selected by Celebes crested macaques (Macaca nigra) in Tangkoko, North Sulawesi, Indonesia. Biodiversitas 24: 6200-6208. Research on the selection of sleeping sites is imperative in providing information on the fitness and survival of a species. We investigated the characteristics of the sleeping sites and the sleeping trees selected by wild Celebes crested macaques (Macaca nigra Desmarest 1822) in North Sulawesi, Indonesia, as well as their spatial and temporal use. The study was conducted in two groups of macaques for nine months (187 study days) from September 2020 to June 2021. These macaques avoided using the same sleeping site on consecutive nights. Two predator encounters (Python reticulatus Schneider 1801) were recorded near the sleeping sites, but pythons caught no monkeys during the study period. The macaques used 58 trees from 13 species as sleeping trees, of which 79% of the sleeping trees were also food trees. M. nigra chose sleeping trees with higher diameter, height, and a bigger Important Value Index than the surroundings. The average distance between sleeping trees and feeding trees in the morning and evening were 203 m and 127 m, respectively. These results suggest that optimal foraging strategy and predator avoidance are important factors in selecting sleeping sites, providing a broader understanding of the habitat preferences of the Critically Endangered M. nigra.